Aplicação das metodologias PMO e TPM para gerenciamento de projetos no contexto da indústria química - Borges, Giovana Gimenes (Universidade Federal de São Carlos, 2024)
Large companies waste resources due to inefficient project management and face challenges in identifying appropriate strategies and methods for project management. In the emerging and dynamic context related to the market that faces significant changes due to the impact of technology and politics, it is essential to prioritize actions and resources in its processes. It is in this context that project management emerges as a fundamental tool for achieving organizational success, so that companies remain competitive and innovative. The case study addresses the application of project management tools in a practical scenario that involves replacing an obsolete reactor in a fictitious biopesticides production plant. The main objective of the work is to demonstrate the relevance and need for Project Management tools in a Chemical Engineering project in the industry. The study also intends to present different project management methodologies, focusing on PMO – Project Management Office approaches (Project Management Office) and TPM (Total Productive Maintenance), exploring the evolution of the mindset over the years in relation to the importance of project management in the industry and how this is a critical factor in reducing risks associated with implementation of projects in the context of engineering. The PMO and TPM methodologies, together with their loss management and prevention tools, were applied as potential solutions and in the hypothetical scenario mentioned, highlighting how project management is essential to ensure that challenging projects are completed successfully, on time and within budget, while maintaining a focus on quality and risk reduction.
Application of the PMO and TPM methodologies for project management in the context of the chemical industry
Keywords: Management; Projects; Chemical engineering; PMO; TPM; Gerenciamento; Projetos; ENGENHARIAS::ENGENHARIA QUIMICA